Tourism Challenges in the Baltic States Since EU Enlargement - Iveta Druva Druvaskalne; Agita Slara (European Regional Science Association (ERSA), 2006)
The paper gives explanation of tourism processes changes in the three Baltic States since 1st May, 2004. The number of tourists are increased in the all three Baltic States during EU enlargement. It does not mean that the benefits from tourism and travel industry is increased at the same figures at the same time because of many tourists are spending small amount of money or they are not spending at all. The main issue is to provide sustainable tourism products for foreign markets, not seperate activities. At the same time it is necessary to develop new sustainable tourism attractions in cities and in rural areas by local initiative if Baltic States wants to increase income from tourism and travel industry.
Keywords: 330